We will compute probabilities "P(Y=1)" and "P(Y=-1)" . Namely, using the formula for infinite geometric series (see https://en.wikipedia.org/wiki/Geometric_progression), we have:
"P(Y=1)=\\sum_{k=1}^{+\\infty}P(X=2k)=\\sum_{k=1}^{+\\infty}\\frac{1}{2^{2k}}=\\frac{1}{4}\\frac{1}{1-\\frac{1}{4}}=\\frac{1}{3}" ;
"P(Y=-1)=\\sum_{k=1}^{+\\infty}P(X=2k-1)=\\sum_{k=1}^{+\\infty}\\frac{1}{2^{{2k-1}}}=\\frac{1}{2}\\frac{1}{1-\\frac{1}{4}}=\\frac{2}{3}" .
Using the formula for the expected value in finite case (see https://en.wikipedia.org/wiki/Expected_value#Finite_case), we get:
"E[Y]=P(Y=1)-P(Y=-1)=-\\frac13\\approx-0.33"
Answer:-0.33
Comments
Leave a comment